Flowering and seeding patterns in primary, secondary and silvopastoral managed Nothofagus antarctica forests in South Patagonia - Soler Esteban, Rosina Matilde; Martínez Pastur, Guillermo José; Lencinas, María Vanessa; Peri, Pablo Luis (Taylor & Francis, 2022)
The success ofthe reproductive process in trees depends on abiotic and biotic factors that determine the final outcome of natural regeneration. Silviculture alters biotic and abiotic factors and results in secondary forest structures. To effectively manage these forests, it is necessary to understand the bottlenecks in reproductive stages using a whole-cycle approach study. The aim ofthis study was to analyse flowering and seeding patterns in primary, secondary and silvopastoral managed Nothofagus antarctica forests, including investigating the pre-dispersion foraging of insects and birds, as well as abscised biomass production. A high percentage of female flowers produced fruits (95 96%) in which the main loss factor before seeding was the abscission ofimmature fruits (11 14%). Seeding was greater in secondary forests (11.4 million ha1), but managed stands presented a higher percentage offlowers resulting in seeds (82%). However, secondary forests had a better seed quality (17% viable seeds), where the main loss factor was empty seeds in all treatments (39 50%). Biotic factors (foraging by insects and birds) were higher in disturbed than primary forests. Nothofagus antarctica produce large quantities of seeds, but abscised immature fruits and empty seeds due to self-incompatibility mechanisms appeared as the major loss factors.